Disinventing/Reinventing competence in everyday communication practices of Japanese and non-Japanese residents in Nigata City, Japan - Martinez, Julius C.; Metila, Romylyn A.; Chiu, Menelea M.; Abaya, Eufracio C.; Baetiong, Lourdes R..; Martin, Ma. Isabel P.; Tupas, Ruanni (Quezon City College of Education, University of the Philippines Diliman, 2019)
Competence is the kernel of language education. It structures language policies, instruction, assessments, materials, and curriculum. It affects the ways the teachers think about their students. It also touches a number of burning questions teachers often grapple with, such as: What does it mean to be competent? How can it be taught and learned? Because competence has a fundamental role in teaching and learning languages, unpacking it should not be taken for granted. By unpacking competence, the present study addresses a number of gaps. First, prevailing theories of competence are insufficient to explain the ways people with diverse linguistic resources communicate. Second, traditional scholarship about competence is limited to questions of practical efficiency in teaching and learning. Lastly, current understanding of competence view language from a colonialist mindset that language is bounded, mentalist, discrete and neutral entity. The present study attempts to fill in these gaps through disinventing and reinventing competence. Through disinvention, the study departs from a notion of competence with colonialist perspectives. Through reinvention, the present study goes beyond traditional scholarship about, and generates alternative understandings of competence. As a project of disinvention, the study gives emphasis to the social and political aspects of competence. Research tradition about competence is concerned about relatively stable forms, grammars, structures, systems, and cognition tied up to discrete, separate languages.
Dissertation (Doctor of Philosophy in Education - Language Education)--University of the Philippines, Diliman
Includes bibliographical references (pages 325-353).
Keywords: Communication; Communicative competence; Communication and culture